Immunization with modified vaccinia virus Ankara prevents eczema vaccinatum in a murine model of atopic dermatitis - Oyoshi, Michiko K. (2011)
Immunization with modified vaccinia virus Ankara (MVA) protects mice with allergic skin inflammation from developing eczema vaccinatum (EV), suggesting that immunization with MVA would be effective in preventing EV in patients with atopic dermatitis.